1993
DOI: 10.1366/0003702934065975
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigations of Malaria Pigment

Abstract: Malaria pigment is generated during the growth of the intraerythrocytic parasite plasmodium. This compound is postulated as a product of haemoglobin degradation and consists of an unknown iron porphyrin compound and an apoprotein. We report here a new spectroscopic investigation on the porphyrin component of intact malaria pigment obtained from in vitro cultures of Plasmodium falciparum without any previous chemical or biochemical treatment of the sample. We demonstrate the use of resonance Raman microspectrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Brémard et al used RRS to characterize hemozoin 92 and Ong et al used RRS to characterize infected RBCs. 93,94 It was mentioned above (Intracellular hemoglobin) that workers at Monash University carried out some of the earliest studies of intracellular hemoglobin 16,39,41 and that, in the years since, two members of the team, Wood and McNaughton, have gone on to do much Raman spectroscopic analysis of pathological erythrocytes.…”
Section: Malaria Malaria Is Caused By a Genus Of Parasites Calledmentioning
confidence: 99%
“…Brémard et al used RRS to characterize hemozoin 92 and Ong et al used RRS to characterize infected RBCs. 93,94 It was mentioned above (Intracellular hemoglobin) that workers at Monash University carried out some of the earliest studies of intracellular hemoglobin 16,39,41 and that, in the years since, two members of the team, Wood and McNaughton, have gone on to do much Raman spectroscopic analysis of pathological erythrocytes.…”
Section: Malaria Malaria Is Caused By a Genus Of Parasites Calledmentioning
confidence: 99%
“…For example, the use of confocal Raman spectroscopy could shed new lights on the electronic structure of hemozoin, a by-product of hemoglobin (Hb) catabolization by the malaria parasite and also an important target site for anti-malarial drugs. 13,14 Significant differences in Raman spectra have been reported for p-RBC and np-RBC in continuous in-vitro culture. 15,16 Therefore, Raman spectroscopy may help in understanding the altered properties of RBCs in malaria patients (m-RBCs).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, hemozoin exhibits a band profile consistent with a 5-coordinate high-spin S = 5/2 heme complex, with strong bands at 1623, 1587, 1569 and 1551 cm -1 , which have been previously assigned [18]. Bands of 1400-1300 cm -1 are mainly associated with pyrrole in-phase breathing vibrations with different phasing [66], the intensity of which varies between Hb and hemozoin.…”
Section: Resonance Raman Studies Investigating the Electronic And Molecmentioning
confidence: 80%
“…Electron paramagnetic resonance and Mössbauer spectroscopy determined that both hemozoin and β-hematin have a single S = 5/2 iron environment in the bulk phase [17]. This result was further supported by a resonance Raman (RR) study by Bré-mard and colleagues who, using RR microspectroscopy, electron paramagnetic resonance spectrometry and magnetic susceptibility measurements, suggested that malaria pigment is a high-spin monomeric Fe(III)PPOH [18]. Powder-diffraction data obtained with synchrotron radiation indicated that β-hematin is linked into dimers through reciprocal iron-carboxylate bonds to one of the propionate side chains and that the dimmers, in turn, form chains linked by hydrogen bonds [7].…”
mentioning
confidence: 77%
See 1 more Smart Citation